PENERAPAN KODE ETIK JURNALISTIK ISLAMI DI ERA MILENIAL - Suf Kasman (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
Journalism ethics and standards comprise principles of ethics and of good practice as applicable to the specific challenges faced by journalists. This subset of media ethics is widely known to journalists as their professional